ORGANIZATIONAL CHANGE AND DEVELOPMENT IN IMPROVING PERFORMANCE EFFECTIVENESS IN THE ERA OF DIGITAL TRANSFORMATION - Ahmad Afan; Baidowi, Mofid; Muh Wahyu Safaat, Andi; Maya Jailani; Tetra Hidayati (Cita konsultindo, 2025)
Rapid technological change and digital transformation have created a new paradigm in the way organizations operate and compete. This research presents a comprehensive analysis of how organizations can improve performance effectiveness through organizational change and development in the context of digital transformation. Based on a systematic review of recent empirical studies, this research identifies critical factors that influence the success of digital transformation, including leadership, organizational culture, digital capabilities, and change management. The results show that successful digital transformation requires a holistic approach that integrates technological, human, and organizational process aspects. Key findings indicate that organizations that succeed in digital transformation have the characteristics of: (1) strong leadership with a clear digital vision, (2) an adaptive and innovative organizational culture, (3) mature digital capabilities, and (4) a systematic change management approach. This study makes a significant contribution to the change management and digital transformation literature by providing a comprehensive framework for understanding and managing organizational change in the digital age. The practical implications of this study can assist organizations in planning and implementing their digital transformation initiatives more effectively.